Peanut mechanized digging regarding to plant population and soil water level - Cristiano Zerbato; Vicente F. A. Silva; Luma S. Torres; Rouverson P. da Silva; Carlos E. A. Furlani (Revista Brasileira de Engenharia Agrícola e Ambiental)
The largest losses in mechanical harvesting of peanuts occur during the stage of digging, and its assessment is still incipient in Brazil. Therefore, the aim of this study was to evaluate the quantitative losses and the performance of the tractor-digger-inverter, according to soil water content and plant populations. The experiment was conducted in a completely randomized block design with a factorial scheme 2 x 3, in which the treatments consisted of two soil, water content (19.3 and 24.8%) and three populations of plants (86,111, 127,603 and 141,144 plants ha-1), with four replications. The quantitative digging losses and the set mechanized performance were evaluated. The largest amount of visible and total losses was found in the population of 141.144 plants ha-1 for the 19.3% soil water content. The harvested material flow and the tractor-digger-inverter performance were not influenced by soil water content and plant population. The water content in the pods was higher in 24.8% soil water content only for the population of 86,111 plants ha-1; the yield was higher in the populations of 141.144 and 127.603 plants ha-1, in the 19.3 e 24.8% soil water content, respectively.